Direct and indirect cost of managing Alzheimer’s disease in the Islamic Republic of Iran - Aajami, Zahra (Iran J Neurol, 2019)
Background: Alzheimer’s disease (AD) affects a large number of adults annually all around the world. The monetary cost of this disorder is huge. This study aims to estimate the cost of AD in Iran by considering stages of disease. Methods: A cross-sectional study was designed from July to December 2017 on 300 AD cases who referred to the Iran Alzheimer’s Association, Tehran, Iran. To calculate costs at different stages of disease, patients were assigned into three groups, based on the Mini-Mental State Exam (MMSE) score. A list of medicines’ prices and health care service costs were prepared. Health care services’ cost was acquired from the book of “Relative value units of health care services in Iran” and the price of medicines was extracted from "Iran’s medicine triple prices list". Patients’ medical records and face to face interview with their caregivers were used for data collection. The perspective of present research was societal. Results: Annually, per person cost of AD in mild, moderate, and severe stages of disease were 434 United States dollars (USD), 1313 USD, and 2480 USD, respectively. Direct non-medical costs (DNMC) had the greatest share of total costs (near half of the whole costs) including 263 USD, 641 USD, and 1257 USD for mild, moderate, and severe stages, respectively. Conclusion: The cost of AD in Iran is lower than the average cost of dementia in upper middle-income countries. In all stages, the biggest part of the cost is associated with patient care and nursing services because patients suffering from AD usually require specialized cares.